ANTICHOLINESTERASE ACTIVITY OF ENDEMIC PLANT EXTRACTS FROM SOQOTRA - Bakthir, Hussein; Ali, Nasser A. Awadh; Arnold, N.; Teichert, A.; Wessjohann, L. (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
A total of 30 chloroform and methanol extracts from the following endemic Soqotran plants Acridocarpus socotranus Olive, Boswellia socotranao Balf.fil, Boswellia elongata Balf. fil., Caralluma socotrana N. Br, Cephalocroton socotranus Balf.f, Croton socotranus Balf. fil.., Dendrosicycos socotrana Balf.f., Dorstenia gigas Schweinf. ex Balf. fil., Eureiandra balfourii Cogn. & Balf. fil., Kalanchoe farinaceae Balf.f, Limonium sokotranum (Vierh) Radcl. Sm), Oldenlandia pulvinata, Pulicaria diversifolia( Balf. and Pulicaria stephanocarpa Balf. were screened for their acetylcholinesterase inhibitory activity by using in vitro Ellman method at 50 and 200 Âµg/ml concentrations. Chloroform extracts of Croton socotranus, Boswellia socotrana, Dorstenia gigas, and Pulicaria stephanocarpa as well as methanol extracts of Eureiandra balfourii exhibited inhibitory activities higher than 50 % at concentration of 200 ïg. At a concentrations of 50 ïg, the chloroform extract of Croton socotranus exhibited an inhibition of 40.6 %.